Influence of cubic texture intensity of hot rolled ferritic non-oriented electrical steels on the microstructure and texture in the final processed material. Issue 1 (April 2015) - Stöcker, A; Schneider, J; Scholze, T; Franke, A; Hermann, H; Kawalla, R
Abstract: The magnetic properties of non-oriented electrical steels are determined by the microstructure and texture of the material. Besides optimum grain size (microstructure) for low values of specific magnetic losses, a high intensity of θ-fibre texture and low intensity of γ-fibre and α-fibre texture is desirable. Each of the processing steps influences the intensity of the θ-fibre in the final processed material. In this paper the interplay of the various processing steps on the intensity of the θ-fibre is regarded for ferritic Iron-Silicon steels with 2.4 wt.% Si and 3.0 wt.% Si.